An Investigation of Factors Motivating Studentâs Study at The International Hotel Management Institute Switzerland - Efendy, Hengky (Binus Business Review, 2010)
Nowadays, in this era of globalisation the hospitality industry needs well educated employees. Therefore the hotel school has to provide human resources to fit any position in the hospitality industry. The author chose the International Hotel Management Institute (IMI)-Switzerland for research too specifically investigates factors affecting studentsâ motivations to study. The authorâs experience was that many students of hospitality are not very motivated to study hotel management. Students get bored while having lectures, are not motivated to go to the library to research, and yet to be educated is the main reasons that students come to IMI to study hospitality. The author has set several objectives in chapter two to ensure the flow of this research. The literature review will be covered in motivating of students study for hotel school education.Literature review which is critically analysed by the author was chosen by the author according the field of study. The sample chosen for this research was motivation students study from first, second, third and fourth year students in IMI- Switzerland Several motivation of this research was the reference book of this field study, and the length of time for making this dissertation. After the primary data were collected and analysed, it was discovered that most of all students in IMI-Switzerland is to have a better chance of getting a job after finishing the course.Â